PERANCANGAN SISTEM PAKAR BERBASIS WEB UNTUK MENDETEKSI KERUSAKAN HANDPHONE DENGAN METODE FORWARD CHAINING - Hariyanto, Eri; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2024)
handphone or cell phones are electronic telecommunication devices that have capabilities and functions resembling computers. Almost all society own and use mobile phones for communication and business purposes, so that smartphones are a mandatory item for their users. Like other electronic goods, if used too often, cellphones are susceptible to damage due to various triggers such as exposure to liquids, falls, or improper use in everyday life. Not many people understand the types of cell phone damage. With the rise of irresponsible service agents who take advantage of people's ignorance in detecting damage to cellphones, a web-based expert system was designed to detect damage to damaged cellphones. With the creation of this system, ordinary people can also get an idea of ​​cell phone damage, often with the help of experts in the field. This system uses PHP as the backend, MYSQL as the database, and uses forward chaining.